A review of Lawshe’s method for calculating content validity in the social sciences - Romero Jeldres, Marcela; Díaz Costa, Elisabet; Faouzi Nadim, Tarik (Frontiers in Education, 2023)
This study aimed to show the usefulness of Lawshe's method (1975) in investigating the content validity of measurement instruments under the strategy of expert judgment. The research reviewed the historical use of Lawshe's method in the social sciences and analyzed the main criticisms of this method using mathematical hypotheses. Subsequently, we experimented with an instrument designed to determine the pedagogical skills possessed by students undertaking initial teacher training in Chile. The results showed that in Lawshe's proposal, it is essential to highlight the need to reconsider the sum of all Content Validity Ratio (CVR) indices for the calculation of the context validity index and not only the indices that exceed the critical Content Validity Index (CVI) given the greater power of discrimination presented by the latter alternative.